2008
DOI: 10.2527/jas.2006-782
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary short-chain fructooligosaccharides on the intestinal microflora of horses subjected to a sudden change in diet

Abstract: Prebiotic compounds, such as short-chain fructooligosaccharides (scFOS), have been shown to improve health, welfare, or both, in several species, but few studies have been conducted in horses, despite the sensitivity of their hindgut microflora. We hypothesized that prebiotic oligosaccharides, known to be able to stabilize the intestinal microflora in other species, would be of importance in horses. Our study was designed to evaluate the effect of scFOS supplementation on the equine intestinal microflora and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 35 publications
7
58
1
1
Order By: Relevance
“…In general, when horses fed a pelleted feed rich in fiber or cereal grain, the cecal total anaerobic bacteria counts were 7.6 log 10 cfu and 7.7 log 10 cfu, respectively (deFombelle et al, 2003). These values are similar to other studies that have cultured total anaerobic bacteria (Medina et al, 2002;Respondek et al, 2008). Studies incorporating an abrupt diet change from all forage to a mixed diet found that total anaerobic bacterial counts increased, and this also occurs in sheep and cattle along with a decreased pH from concentrate feeding (Grubb and Dehority, 1975;Goodson et al, 1988).…”
Section: Influence Of Diet On the Cecal Environmentsupporting
confidence: 87%
“…In general, when horses fed a pelleted feed rich in fiber or cereal grain, the cecal total anaerobic bacteria counts were 7.6 log 10 cfu and 7.7 log 10 cfu, respectively (deFombelle et al, 2003). These values are similar to other studies that have cultured total anaerobic bacteria (Medina et al, 2002;Respondek et al, 2008). Studies incorporating an abrupt diet change from all forage to a mixed diet found that total anaerobic bacterial counts increased, and this also occurs in sheep and cattle along with a decreased pH from concentrate feeding (Grubb and Dehority, 1975;Goodson et al, 1988).…”
Section: Influence Of Diet On the Cecal Environmentsupporting
confidence: 87%
“…Of the limited publications on the effects of oligofructose on colonic bacterial populations in horses and other species (Beynen et al, 2002;Macfarlane et al, 2006;Milinovich et al, 2007;Respondek et al, 2008), all report a significant increase in streptococci. If EHSS are responsible for laminitis, as we suggest, the effect of dietary supplementation with oligofructose at pre-biotic dosage rates needs to be studied promptly.…”
Section: Discussionmentioning
confidence: 99%
“…As their typical diet is high in roughage and feedstuffs that are consumed through out the day, prebiotic interventions might help improve effectiveness of fermentation [150][151][152] .…”
Section: Conferring a Health Benefitmentioning
confidence: 99%